Matematični model za simulacijo in optimizacijo procesov v parno-kompresijskih hladilnih sistemih - Lorbek, Luka (visokošolska dela, 2021)
Existing capillary tube models rely on general friction factor correlations, which were not designed for the flow of refrigerant through these tubes. Additionally, it is unknown whether the two-phase flow in them is homo- or heterogeneous. This work presents the development of an improved friction factor correlation, which was implemented in a numerical capillary tube model. The accuracy of the latter increased by (plus-minus)1,3 % as a result of this. A visualization of the flow was also performed. It showed that the flow is a predominantly heterogeneous plug flow. In addition to the performed experiments, an algorithm for the optimization of capillary tube-suction line heat exchangers was also developed. Comparison of different optimization algorithms showed that evolutionary algorithms performed most favourably.
Keywords: capillary tubes; Disertacije; dissertations; Hladilni sistemi; hlajenje; kapilarne cevi; matematična optimizacija; Matematični modeli; mathematical optimization; numerical modeling; numerično modeliranje; optimizacija; parno-kompresijski sistemi; refrigerant flow; refrigeration; simulacija; tok hladiva; vapor-compression systems